2015
DOI: 10.1371/journal.pntd.0003957
|View full text |Cite|
|
Sign up to set email alerts
|

Weather Regulates Location, Timing, and Intensity of Dengue Virus Transmission between Humans and Mosquitoes

Abstract: BackgroundDengue is one of the most aggressively expanding mosquito-transmitted viruses. The human burden approaches 400 million infections annually. Complex transmission dynamics pose challenges for predicting location, timing, and magnitude of risk; thus, models are needed to guide prevention strategies and policy development locally and globally. Weather regulates transmission-potential via its effects on vector dynamics. An important gap in understanding risk and roadblock in model development is an empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 47 publications
2
45
0
2
Order By: Relevance
“…This stood in contrast to Hanoi (annual average temperature of 23.6°C), where the opposite was observed. This relationship between dengue transmission, temperature and humidity was modeled in a high-resolution profile of these factors across space in Peru [17]. Our findings are consistent with this study, which demonstrated that dengue transmission potential was dependent on the duration within an optimal temperature range and was amplified exponentially by high humidity [17].…”
Section: Discussionsupporting
confidence: 88%
“…This stood in contrast to Hanoi (annual average temperature of 23.6°C), where the opposite was observed. This relationship between dengue transmission, temperature and humidity was modeled in a high-resolution profile of these factors across space in Peru [17]. Our findings are consistent with this study, which demonstrated that dengue transmission potential was dependent on the duration within an optimal temperature range and was amplified exponentially by high humidity [17].…”
Section: Discussionsupporting
confidence: 88%
“…The average temperature is around 27 °C, and mean cumulative rainfall is about 2500 mm a year. The warm and wet weather coupled with high humidity is conducive to the development of Aedes mosquitoes, viral replication, and transmission of dengue year-round [3•, 18••, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…Seasonal infectious disease surveillance data often shows regular patterns of onset, peak, and nadir . The goal of ALERT is to assign a static value to the incidence threshold level used to define epidemic onset.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal infectious disease surveillance data often shows regular patterns of onset, peak, and nadir. 24 The goal of ALERT is to assign a static value to the incidence threshold level used to define epidemic onset. Using historical information from a local surveillance system (eg, a hospital or city), ALERT assists in the choosing of an appropriate time to begin a particular intervention that would cover the period of highest seasonal respiratory virus activity.…”
Section: Introductionmentioning
confidence: 99%